The Implementation of the Regional Goverment Accounting System, Accounting Literacy and Internal Control on Performance Accountability at the Department of Community and Village Empowerment in Trenggalek Regency - Krissantina Eferyn; Meme Rukmini; Gandung Satriyono; Eka Agustina; Bima Fatkul Khusna Arinda (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the application of the local government accounting system, accounting literacyand internal control over performance accountability at the Community and Village Empowerment Office of Trenggalek Regency. The research method used by distributing questionnaires to 42 respondents at the Community and Village Empowerment Office of Trenggalek Regency, to test the results of this study using multiple linear regression analysis with the help of SPSS version 26. The results of this study show that the Local Government Accounting System affects Performance Accountability, Accounting Literacy affects Performance Accountability, and Internal Control affects Performance Accountability. This research contributes to all employees in the Community and Village Empowerment Office that it is important to understand the local government accounting system, accounting literacy and internal control when doing work so that they are able to increase performance accountability at the Community and Village Empowerment Office.The limitation of this research is that the number of respondents is less than 50 respondents and can be further refined by adding variables in testing performance accountability.